2016
DOI: 10.1371/journal.pone.0161568
|View full text |Cite
|
Sign up to set email alerts
|

Re-Evaluating the Geological Evidence for Late Holocene Marine Incursion Events along the Guerrero Seismic Gap on the Pacific Coast of Mexico

Abstract: Despite the large number of tsunamis that impact Mexico’s Pacific coast, stratigraphic studies focusing on geological impacts are scanty, making it difficult to assess the long-term risks for this vulnerable region. Surface samples and six cores were taken from Laguna Mitla near Acapulco to examine sedimentological and geochemical evidence for marine incursion events. Sediment cores collected from behind the beach barrier are dominated by intercalated layers of peat and inorganic sediments, mostly silt and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…More broadly, the posited regional tectonic processes (coseismic subsidence and interseismic uplift) are the reverse of that exhibited by historical events, which are characterized by coseismic uplift and interseismic subsidence. This inconsistency was suggested to have resulted from a megathrust earthquake so much larger than normal that it ruptured the plate interface, thereby reversing the normal process (Ramírez-Herrera et al, 2009, but no evidence of such a cataclysmic event is found in any of our stratigraphic records from Laguna Mitla (Bianchette et al, 2016).…”
Section: Tectonic Controlsmentioning
confidence: 73%
“…More broadly, the posited regional tectonic processes (coseismic subsidence and interseismic uplift) are the reverse of that exhibited by historical events, which are characterized by coseismic uplift and interseismic subsidence. This inconsistency was suggested to have resulted from a megathrust earthquake so much larger than normal that it ruptured the plate interface, thereby reversing the normal process (Ramírez-Herrera et al, 2009, but no evidence of such a cataclysmic event is found in any of our stratigraphic records from Laguna Mitla (Bianchette et al, 2016).…”
Section: Tectonic Controlsmentioning
confidence: 73%
“…In particular, significance testing of the surface samples taken along a marine‐to‐terrestrial gradient with gradually thinning storm signals shows that the elemental concentration of Cl and Sr and Cl/Br ratio has the closest association with storm deposits from Hurricane Wilma among the 9 XRF parameters. High content of Sr has been described as an indicator of marine incursions in previous studies from southwestern Florida (Van Soelen et al, 2012; Yao & Liu, 2018) and elsewhere (Bianchette et al, 2016; Liu et al, 2015; McCloskey et al, 2015, 2018; McCloskey & Liu, 2013; Ramírez‐Herrera et al, 2012; Woodruff et al, 2009). This element is likely associated with marine gastropods in offshore environment and introduced to coastal area by storm surges (Yao & Liu, 2017; Yao et al, 2015, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…During Zone‐2, although much closer to the sea in comparison to Zone‐1, our study site, which is currently at the mouth of the Shark River Slough, would still have been at some distance inland from the former shoreline and beyond the distance reachable by marine sediments carried by storm surge waters during the period from ~3,500 to 1,150 cal yr BP. This explains the negative background values of Sr, a common indicator of marine sediments (Bianchette et al, 2016; McCloskey & Liu, 2013; McCloskey et al, 2015; Ramírez‐Herrera et al, 2012; Yao & Liu, 2018), throughout Zone‐2. However, Cl and Cl/Br are associated more with saltwater intrusion than the delivery of marine sediments (Liu et al, 2015; McCloskey et al, 2018; Yao et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this regard, trace metals are one of the most promising sentinels of tsunamigenic deposits both during the Holocene and nowadays (Veerasingam et al, 2014;Bianchette et al, 2016). Chemical signatures of (palaeo-)tsunamis have been reviewed in the last years, with exciting perspectives for the future development of this field (Chagué-Goff, 2010;Nelson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%